2021
DOI: 10.1177/17474930211009806
|View full text |Cite
|
Sign up to set email alerts
|

ASPECTS-based selection for late endovascular treatment: a retrospective two-site cohort study

Abstract: Introduction The DAWN trial demonstrated the effectiveness of late endovascular treatment (EVT) in acute ischemic stroke (AIS) patients selected on the basis of a clinical-core mismatch. We explored in a real-world sample of EVT patients if a clinical-ASPECTS (Alberta Stroke Program Early CT Score) mismatch was associated with an outcome benefit after late EVT. Methods We retrospectively analysed all consecutive AIS patients admitted 6-24 hours after last proof of good health in two stroke centres, with ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…In a 2-site analysis of patients in the extended time window in Switzerland, MT was effective in the presence of a clinical-ASPECTS mismatch as defined by the DAWN study criteria but not effective in its absence. Another study suggested that NCCT-ASPECTS–based selection paradigms for late MT have similar 90-day outcomes as the DAWN and DEFUSE-3 studies. In a network of stroke centers in Houston, Texas, hospitals with NCCT as the initial imaging choice were more likely to perform MT than hospitals with NCCT and CTP as the primary approach, without any difference in clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2-site analysis of patients in the extended time window in Switzerland, MT was effective in the presence of a clinical-ASPECTS mismatch as defined by the DAWN study criteria but not effective in its absence. Another study suggested that NCCT-ASPECTS–based selection paradigms for late MT have similar 90-day outcomes as the DAWN and DEFUSE-3 studies. In a network of stroke centers in Houston, Texas, hospitals with NCCT as the initial imaging choice were more likely to perform MT than hospitals with NCCT and CTP as the primary approach, without any difference in clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One out of 18 studies prospectively recruited patients 47. The majority of the remaining studies (n=13) conducted post-hoc analyses of prospective trial data or endovascular therapy registries, that is, patient and imaging characteristics were retrospectively reviewed according to different predefined triage models and reported along with efficacy and safety outcomes 48–59. Four studies reported observational data from clinical practice,60–63 and one study analysed pooled data from several randomised clinical trials 64.…”
Section: Basic Imaging Selection Paradigms In the Literaturementioning
confidence: 99%
“…Studies providing group comparisons adhered to either of two principle study designs: (1) patients meeting the criteria of a basic imaging paradigm presenting 6–24 hours after stroke onset (basic LATE -group) were compared with patients routinely selected for endovascular therapy without the use of advanced imaging within 6 hours of stroke onset (basic EARLY -group) according to guidelines (n=5),47 49 52 60 62 or (2) within 6–24 hours after stroke onset, patients who fulfilled basic imaging criteria (late BASIC -group) were compared with patients meeting perfusion imaging criteria (late CTP -group) that matched or closely referred to the DAWN/DEFUSE3 selection criteria (n=10) 48 50 53–60 63. Seven studies additionally reported outcome data of patients not treated with endovascular therapy 47 48 51 53 55 58 64…”
Section: Basic Imaging Selection Paradigms In the Literaturementioning
confidence: 99%
See 2 more Smart Citations